A Correlation Between The Utilization Of Kia Book And Compliance With Complete Basic Immunization In Infants Aged 0-11 Months At Kampung Delima Health Center, Rejang Lebong Regency, In 2024 - Lensiana, Lensiana; Putri, Yesi; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2025)
Immunization is the most effective primary prevention against infectious diseases, protecting individuals from serious illnesses and preventing the spread of contagious diseases (Irawati, 2020). Immunization is carried out to induce or enhance immunity against certain diseases; if not done, it can increase the risk of exposure to diseases with severe symptoms (Hudhah, 2020). The purpose of this study is to determine the correlation between the use of the Maternal and Child Health (MCH) Book and compliance with complete basic immunization in infants aged 0-11 months at Kampung Delima Public Health Center, Rejang Lebong Regency, in 2024.This study uses an analytical research design with a cross-sectional approach. The measurement of variables is conducted at a specific point in time, meaning that subjects are observed and measured simultaneously. The sampling technique used is purposive sampling, with a total of 69 respondents.The results of the Chi-square test show that there is a correlation between the use of the MCH Book and compliance with complete basic immunization in infants aged 0-11 months, with a chi-square result of p-value 0.001 (α<0.05). Thus, it can be concluded that there is a correlation between the use of the Maternal and Child Health Book and compliance with complete basic immunization in infants aged 0-11 months at Kampung Delima Public Health Center, Rejang Lebong Regency, in 2024.It is recommended that the public health center utilize this information as a means of evaluation, particularly in increasing the coverage of complete basic immunization in infants